Macrophage migration inhibitory factor protects from nonmelanoma epidermal tumors by regulating the number of antigen‐presenting cells in skin. Issue 2 (19th October 2016) - Brocks, Tania; Fedorchenko, Oleg; Schliermann, Nicola; Stein, Astrid; Moll, Ute M.; Seegobin, Seth; Dewor, Manfred; Hallek, Michael; Marquardt, Yvonne; Fietkau, Katharina; Heise, Ruth; Huth, Sebastian; et al.
ABSTRACT: The response of the skin to harmful environmental agents is shaped decisively by the status of the immune system. Keratinocytes constitutively express and secrete the chemokine‐like mediator, macrophage migration inhibitory factor (MIF), more strongly than dermal fibroblasts, thereby creating a MIF gradient in skin. By using global and epidermis‐restricted Mif ‐knockout ( Mif -/- and K14‐Cre +/tg; Mi ffl/fl ) mice, we found that MIF both recruits and maintains antigen‐presenting cells in the dermis/epidermis. The reduced presence of antigen‐presenting cells in the absence of MIF was associated with accelerated and increased formation of nonmelanoma skin tumors during chemical carcinogenesis. Our results demonstrate that MIF is essential for maintaining innate immunity in skin. Loss of keratinocyte‐derived MIF leads to a loss of control of epithelial skin tumor formation in chemical skin carcinogenesis, which highlights an unexpected tumor‐suppressive activity of MIF in murine skin.—Brocks, T., Fedorchenko, O., Schliermann, N., Stein, A., Moll, U. M., Seegobin, S., Dewor, M., Hallek, M., Marquardt, Y., Fietkau, K., Heise, R., Huth, S., Pfister, H., Bernhagen, J., Bucala, R., Baron, J. M., Fingerle‐Rowson, G. Macrophage migration inhibitory factor protects from nonmelanoma epidermal tumors by regulating the number of antigen‐presenting cells in skin. FASEB J. 31, 526–543 (2017). http://www.fasebj.org